2021
DOI: 10.1186/s12944-021-01553-2
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model based on platelet parameters, lipid levels, and angiographic characteristics to predict in-stent restenosis in coronary artery disease patients implanted with drug-eluting stents

Abstract: Background The present study was aimed to establish a prediction model for in-stent restenosis (ISR) in subjects who had undergone percutaneous coronary intervention (PCI) with drug-eluting stents (DESs). Materials and methods A retrospective cohort study was conducted. From September 2010 to September 2013, we included 968 subjects who had received coronary follow-up angiography after primary PCI. The logistic regression analysis, receiver operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Another systemic factor noted in our study to be closely related to ISR after PCI is preoperative neutrophil/ lymphocyte ratio, the index associated with inflammatory response and neointimal proliferation, 4,5,17,18 which was consistent with the previous research that neutrophil/lymphocyte is a strong inflammatory marker [19][20][21][22] and closely associated with Cardiovascular disease. In contrast to previous reports, we also discovered that RC had a higher predictive value for ISR than LDL-C.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another systemic factor noted in our study to be closely related to ISR after PCI is preoperative neutrophil/ lymphocyte ratio, the index associated with inflammatory response and neointimal proliferation, 4,5,17,18 which was consistent with the previous research that neutrophil/lymphocyte is a strong inflammatory marker [19][20][21][22] and closely associated with Cardiovascular disease. In contrast to previous reports, we also discovered that RC had a higher predictive value for ISR than LDL-C.…”
Section: Discussionsupporting
confidence: 92%
“…3 Life-threatening consequences can arise should the ISR continue to deteriorate without prompt recognition and treatment. Therefore, early identification of risk factors for ISR is crucial in preventing major Previous studies 5,6 summarized the predictors of ISR as follows: medication history (eg, clopidogrel), prior PCI, stent characteristics, and some indicators concerning inflammatory responses and lipid metabolism (eg, TC, LDL-C, CRP, monocyte). 11 Similar to the previous studies, 11 we also found that monocytes can be one of the independent risk factors for ISR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have shown that dyslipidemia and ISR are indissolubly linked. 6 To the best of our knowledge, the majority of the previous related literature 7 , 8 has concentrated on investigating the impact of low-density lipoprotein cholesterol (LDL-C) levels on ISR. However, a growing number of studies have demonstrated that patients are still at considerable risk of developing cardiovascular disease even after lowering LDL-C to recommended concentrations and controlling other risk factors (eg, hypertension and diabetes).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there have not been much data to bear out the relationship between RC and ISR. What is more, most of the published studies 8 , 10 , 11 , 15 are retrospective with small sample sizes and use multi-factor logistic regression statistics. It is well known that retrospective studies have many confounding factors and that multifactor logistic regression may suffer from overfitting and covariance, so we attempted to address this by reducing the dimensionality 16 (using LASSO regression).…”
Section: Introductionmentioning
confidence: 99%